Ultrasensitive and uniform surface-enhanced Raman scattering substrates for the methidathion detection - Guanzhou Lin; Jia Zhu; Meizhang Wu; Peimin Lu; Wengang Wu (AIP Advances, 2019)
In this paper, we proposed a rapid method of detecting Methidathion pesticides by surface enhanced Raman scattering (SERS). In the method, Ag nanoparticles (AgNPs) are synthesized by the modified Tollens technique and deposited on glass slides to become simple detection arrays for SERS detection. The AgNPs synthesis used in this research is environmentally friendly and does not produce harmful substances to the environment. Through measuring/investigating the SERS signals of Rhodamine 6G under different concentrations, the preparation process and process parameters of the detection substrate are determined. The Methidathion detection limit reaches 0.1 ppm based on the substrates. This work lays a foundation for preparation of large-scale SERS detection arrays in the future.